Pengaruh Literasi Keuangan Terhadap Perilaku Inovasi Produk Hijau dan Inovasi Proses Hijau di Moderasi Gender Pada Usaha Kecil dan Menengah di Boyolali - Ashari, Rosa Zulfah; Sabandi, Muhammad (Jambura Economic Education Journal, 2025)
Financial literacy is a strategic issue that has increasingly gained attention in various economic studies, particularly in relation to strengthening the innovative capacity of business actors. However, empirical studies linking financial literacy to green innovation behavior, especially in the context of Micro, Small, and Medium Enterprises (MSMEs), remain limited. This study aims to: (1) analyze the influence of financial literacy on green product innovation behavior among MSMEs in Boyolali Regency; (2) examine the effect of financial literacy on green process innovation behavior; and (3) investigate the role of gender as a moderating variable in the relationship between financial literacy and both types of innovation. A quantitative approach is employed in this research through a survey method involving 397 MSME actors selected using accidental sampling. Data were collected using an online questionnaire distributed via the Google Forms platform. Validity testing was conducted using convergent and discriminant validity approaches, while reliability was measured through Cronbach’s Alpha and composite reliability. Data analysis includes descriptive statistics, multicollinearity testing, goodness-of-fit testing, and moderating regression analysis. The results indicate that: (1) financial literacy has a positive and significant influence on green product innovation; (2) financial literacy also significantly enhances green process innovation; and (3) gender plays a significant moderating role in strengthening the relationship between financial literacy and both types of green innovation. These findings not only enrich the literature from the perspective of Human Capital Theory but also provide practical implications for enhancing the innovative capacity of MSMEs in the face of sustainable development challenges.